Proceedings of the IIIT Lunar Calendar Conference - Ahmad, Imad-Ad-Dean (International Institute of Islamic Thought, 1998)
This volume brings together both the elementary scientific facts that any lunar calendar formulation cannot ignore and a summary of the pressing scientific questions of particular interest to the Islamic calendar. Scientific aspects of the problem are thoroughly reviewed without prejudicing the argument in purely Islamic juridical questions and differences. The results are of great significance to both Islamic scholars and the general Muslim public. The papers presented are of a high scientific quality and are followed by a unanimous statement of the professional astronomers on the scientific questions. If these conclusions are followed, the varying sets of conventions used by different Islamic populations can be made selfconsistent and free from scientific errors, even if they still differ from each other. This new edition allows the correction of errors in the first edition, makes the style more uniform among the papers, and improves the articles' graphs and figures. It aims to serve as an effective tool for addressing the calendrical issues that motivated the conference more than being merely a historical record. A new Afterword summarizes refinements in the scientific issues that have taken place in the ten years since the conference, many of which were prompted by the work presented here.